NFM-01. NF105: A PHASE II PROSPECTIVE STUDY OF CABOZANTINIB (XL184) FOR PLEXIFORM NEUROFIBROMAS IN SUBJECTS WITH NEUROFIBROMATOSIS TYPE 1: A NEUROFIBROMATOSIS CLINICAL TRIAL CONSORTIUM (NFCTC) STUDY. Issue 2 (22nd June 2018) - Shih, Chie-Schin; Blakely, Jaishri; Clapp, Wade; Wolters, Pam; Dombi, Eva; Cutter, Gary; Ullrich, Nichole; Allen, Jeffrey; Packer, Roger; Goldman, Stewart; Gutmann, David; Plotkin, Scott; et al.
Abstract: BACKGROUND: Plexiform neurofibromas (PNs) are histologically complex peripheral nerve sheath tumors composed of Schwann cells and fibrocytes. Pre-clinical models have demonstrated that altering the microenvironment with molecular targeting therapy may lead to the shrinkage of PN. Here we test the activity of Cabozantinib, a tyrosine kinase inhibitor of KIT, MET, VEGF, and AXL, in adolescents and adults with NF1-associated PN. METHODS: The NFCTC conducted a study (NCT02101736) evaluating Cabozantinib in subjects ≥16 years with clinically significant PN. Response was determined by MRI assessment of tumor volume. Cabozantinib was administered daily on a continuous dosing schedule for up to 2 years. Starting dose was 40 mg oral daily dose with a dose escalation to 60 mg. Success was determined as ≥ 25% of subjects achieving and maintaining ≥ 20% decrease in tumor volume. RESULTS: 19 evaluable subjects were assessed with a mean age of 23. Subjects were evaluable if they completed at least 1 cycle of therapy and had at least one follow-up tumor imaging. 4 subjects were not evaluable due to enrollment error (n=2), withdrawal during cycle 1 (n=1), ineligible due to eligibility exclusions (n=1). Eight patients (42%) met criteria for PR by 1 year. No subjects had PN progression. Common toxicities were gastrointestinal, hypothyroidism, fatigue, headaches, skin and leukopenia. Three subjects experiencing grade 3 SAEs remained on study after dose reductions. CONCLUSIONS: Cabozantinib demonstrated activity and was well tolerated in patients with clinically significant PN. This trial will be expanded to include a cohort of children <16 years.